Robotic Vision Based PCB Inspection with IOT Interface - Gobee, S.; Durairajah, V.; Xin, K.; Jie, L.L. (2018 3rd International Conference on Control, Robotics and Cybernetics (CRC), 2018)
The purpose of the project is to design a fully automated vision inspection system as well as a pick and place system. This system aims is to be able to perform vision inspection on PCB board to identify the quality of such product before pushing the product to the pick and place system for product segregation. The next aim of this project is also to ensure there are information continuity from machine to another machine to minimize human labor while ensuring high job traceability using IOT monitoring. Furthermore, information gathered from the station which are captured the sensor and vision from the machine can then be viewed either on the station or through the web page. This allows high flexibility in terms of accessing to information from machine as well as monitoring of the condition process of the machine without being physically present. In addition, this project also requires less labor due to fully automation where PCB are push to the next station using the conveyor system which means less time wasted on human transporting product from one machine to another and thus optimizing the entire process flow. Lastly, information gathered from machine on the production short floor are all stored on the database which can be integrate through the company database or through cloud base providing huge flexibility for easy integration of such system into any production line.